The Relevance of Digital Skills of OTKP Graduates to the Needs of the World of Work in the Digital Era - Agustriyono, Dedy; Nurhadi, Didik; Nurjanah, Nunung (STAI Miftahul Ula Nganjuk, 2025)
This study aims to analyze the relevance of digital skills among graduates of the Office Automation and Governance (OTKP) vocational program at SMK Negeri 1 Bandung with the needs of the labor market in the digital era. The research employed a qualitative case study approach involving productive teachers, graduates, and industry representatives as key informants. Data were collected through in-depth interviews, participant observation, and documentation, then analyzed using Miles and Huberman’s interactive model. The results indicate that graduates possess strong basic digital skills such as office software operation and online communication, but exhibit limited competence in virtual collaboration, cloud-based data management, and digital security. The skill gap is influenced by curriculum limitations, insufficient teacher training, and inadequate digital facilities. The study highlights the importance of strengthening the link and match between vocational schools and industries, as well as integrating adaptive digital skills into vocational curricula. The implication of this study emphasizes the need for developing a digital project-based learning model to enhance graduates’ employability and adaptability in the digital transformation era.